(untitled) (Research, Society and Development, 2021)
Regional development of tourism in Brazil is presented as an important alternative to promote the implementation of public policies aimed at social inclusion and overcoming of the different barriers and challenges so as to render tourism that is feasible according to the Environmental Sustainability Principles. Viewing from the perspective of sustainability within the policy of regional development, tourism should be structured under three basic dimensions: i) economic; ii) social and iii) environmental. Based on this framework, the aim of this paper is to analyze the "Program of Regionalization of Tourism" in Brazil in order to make possible the design of its global role a as a positive tool for the socioeconomic development of Brazilian tourism. For this purpose, the study presumes that tourism as an activity can minimize the negative economic, environmental and social impacts which result from its insertion in natural ecosystems and communities, generating benefits for society. We use basic tools of document analysis to interpret the data from Tourism Regionalization Program, an integral part of the Brazilian National Tourism Plan. The results serve as a basis for targeting tourism as an attractive activity with considerable potential to develop Brazilian regions, although demanding that the peculiarities of cities and populations be considered. It was observed that, as to sustainability, special attention should also be given to social, cultural, and environmental aspects in order to turn the tourism process into a vehicle able to promote sustainable growth, through the achievement of the imperatives of economic development, while minimizing negative social, cultural, and environmental impacts.